Bytelearn - cat image with glassesAI tutor

Welcome to Bytelearn!

Let’s check out your problem:

Prove by induction that the sum of the first 
n positive odd integers is 
n^(2).

Prove by induction that the sum of the first nn positive odd integers is n2n^{2}.

Full solution

Q. Prove by induction that the sum of the first nn positive odd integers is n2n^{2}.
  1. Base Case of Induction: Let's start with the base case of induction, which is n=1n = 1. The first positive odd integer is 11. We need to check if the sum of the first odd integer equals 121^2. Sum for n=1n = 1: 11 12=11^2 = 1 Since both are equal, the base case holds true.
  2. Assumption for Positive Integer: Now, let's assume that the statement is true for some positive integer kk, which is our induction hypothesis.\newlineThis means we assume the sum of the first kk positive odd integers is k2k^2.\newlineSum for n=kn = k: 1+3+5++(2k1)=k21 + 3 + 5 + \ldots + (2k - 1) = k^2\newlineThis is our assumption and we will use it to prove the statement for n=k+1n = k + 1.
  3. Proving Statement for n=k+1n = k + 1: Next, we need to show that if the statement is true for n=kn = k, then it must also be true for n=k+1n = k + 1. The sum of the first k+1k + 1 positive odd integers would be the sum of the first kk odd integers plus the next odd integer, which is 2(k+1)12(k + 1) - 1. Sum for n=k+1n = k + 1: 1+3+5++(2k1)+[2(k+1)1]1 + 3 + 5 + \ldots + (2k - 1) + [2(k + 1) - 1] Using our induction hypothesis, we can replace the sum of the first kk odd integers with k2k^2. So, Sum for n=k+1n = k + 1: n=kn = k11
  4. Simplifying the Expression: Now, let's simplify the expression for the sum of the first k+1k + 1 odd integers.\newlineSum for n=k+1n = k + 1: k2+[2k+21]k^2 + [2k + 2 - 1]\newlineSum for n=k+1n = k + 1: k2+2k+1k^2 + 2k + 1\newlineSum for n=k+1n = k + 1: (k+1)2(k + 1)^2\newlineThis shows that the sum of the first k+1k + 1 positive odd integers is indeed (k+1)2(k + 1)^2, which is what we needed to prove.

More problems from Positive and negative square roots